2012
DOI: 10.1097/tp.0b013e318247a7b7
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the British Transplantation Society/Renal Association UK Guidelines for Living Donor Kidney Transplantation

Abstract: The third edition of the joint British Transplantation Society/Renal Association guidelines for living donor kidney transplantation was published in May 2011. The guideline has been extensively revised since the previous edition in 2005 and has used the GRADE system to rate the strength of evidence and recommendations. This article summarizes the statements of recommendation contained in the guideline, which provide a framework for the delivery of living kidney donation in the United Kingdom and may be of wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 4 publications
4
96
0
2
Order By: Relevance
“…It did not, however, undertake a "Graded Evidence Review" of the living kidney donation literature, as Canadian Blood Services and the Committee are supporting the Graded Evidence Review being undertaken by the Kidney Disease: Improving Global Health Outcomes (KDIGO). 1 The Living Donation Advisory Committee will review the reports published by KDIGO as they become available and will make revisions to the Protocol where appropriate.…”
Section: Evidence Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It did not, however, undertake a "Graded Evidence Review" of the living kidney donation literature, as Canadian Blood Services and the Committee are supporting the Graded Evidence Review being undertaken by the Kidney Disease: Improving Global Health Outcomes (KDIGO). 1 The Living Donation Advisory Committee will review the reports published by KDIGO as they become available and will make revisions to the Protocol where appropriate.…”
Section: Evidence Reviewmentioning
confidence: 99%
“…(1) Additional testing will be based on the specific findings from general screening and the potential donor's medical, sexual, and social history: (D) Acceptance Criteria (1) The potential donor has no identifiable infection or risk of infection that would cause an unacceptable risk or harm to the recipient. (2) The potential donor has not been skin-tested for TB and is from a documented low-risk population.…”
Section: (C) Additional Testingmentioning
confidence: 99%
“…EC is the most common malignancy of the female genital tract, and is typically seen in post-menopausal women [12]. Patients with EC are always diagnosed at early stages and have a good prognosis with a 5-year overall survival rate greater than 85% [48].…”
Section: Endometrial Cancer (Ec)mentioning
confidence: 99%
“…Suggested approach to donor utilization is given for each category, recognizing the primacy of individual clinical judgment and often emergent clinical circumstances [9]. According to the third edition (May 2011) of United Kingdom guidelines for living donor kidney transplantation [12], recommendations regarding donor malignancy can be summarized in Table 3.…”
Section: Risk Category Assignment To Specific Tumorsmentioning
confidence: 99%
“…Most centers accept donors as long as they have absolute measured glomerular filtration rate above a set limit of 70 or 80 ml/ min [44]. Others have suggested that the focus should be to predict the donor's post-donation estimated glomerular filtration rate normalized for body surface area [45]. Also, there are differences in how donor renal function is measured.…”
Section: Consequences For Donor Evaluation and Donor Selectionmentioning
confidence: 99%